TVET Research Organizations and Scientific Communities: Challenges to the Institutionalization of TVET Research - Wittig, Wolfgang [Verfasser]; Lauterbach, Uwe [Verfasser]; Grollmann, Philipp [Verfasser] (My University, 2009)
"This chapter provides an overview of the extent and the shape of the organization of TVET research on technical and vocational education and training (TVET) and its variations across different countries and supra-national organizations. This will be carried out by describing some fundamental challenges regarding the instituionalization of TVET research, reporting about the form of TVET research in different national and supra-national contexts, and then summarizing and pointing out some future directions." (Autorenreferat, BIBB-Doku)
Keywords: I 1 Internationale Berufsbildung; I 2.1 Deutschland; I 2.2.1 Westeuropa; I 2.3.5 Australien, Ozeanien; I 2.3.4 Asien; I 2.3.2 Nordamerika; I 1.5 Internationale Organisationen & Institutionen; Berufsbildungsforschung; Internationaler Vergleich; Australien; China; Frankreich; Bundesrepublik Deutschland; Vereinigtes Königreich; USA; Internationale Organisation; Internationale Zusammenarbeit